EFFECT OF GRAIN INTERACTIONS ON THE FREQUENCY DEPENDENCE OF MAGNETIC SUSCEPTIBILITY - Muxworthy A.R. (My University, 2001)
Environmental systems often contain superparamagnetic (SP) grains that cause a frequency dependence of low-field magnetic susceptibility (κfd). Previous models for κfd have been for non-interacting regimes, whereas environmental systems often display characteristics of magnetic interactions. In this paper, the magnetic susceptibility (κ) and κfd have been modelled for weakly interacting assemblages of single-domain (SD) grains of magnetite, near the SP and stable SD threshold known as the blocking volume, vb. Weak interactions between SP grains effectively increase the anisotropy, which reduces vb. The relationship between the grain distribution and the reduced vb causes a decrease in the peak values of κfd, and can reduce κfd by over 50 per cent for certain grain distributions. This helps to explain why κfd values for natural samples are very rarely seen above ≈ 15 per cent, as the effect of interactions is seen to reduce maximum κfd >20 per cent in non-interacting models to values <20 per cent for the same grain distribution. however, it is also found that reduction of vb as a result of interactions can also increase κfd for certain grain distributions. The model only accommodates weakly interacting systems, as the behaviour of strongly interacting SP grains is not well understood, and no analytical formulation has yet been made.
Keywords: ENVIRONMENTAL MAGNETISM; MAGNETIC INTERACTIONS; MAGNETIC SUSCEPTIBILITY; SP-SSD TRANSITION